Application of health education based on PRECEDE-PROCEED model in cardiac rehabilitation exercise after pacemaker implantation (基于格林模式的健康教育在心脏起搏器植入术后患者运动康复中的应用) - QU Junmei (曲军妹) (中西医结合护理)
Objective To investigate the effect of PRECEDE-PROCEED model-based health education on exercise tolerance and cardiac recovery in patients after pacemaker implantation. Methods Totally 98 patients pacemaker implantation were divided into the control group and study group, with 49 cases in each group. The control group received routine health education, while the study group was given health education based on PRECEDE-PROCEED model for 3 months. The score of Chinese Cardiovascular Quality of Life Questionnaire (CCQQ), 6-minute Walking Distance (6MWT), level of NT-ProBNP and Left Ventricular Ejection Fraction(LVEF) of two groups were compared. Results At three months after surgery, patients in the study group achieved a higher score of CQQC, longer 6MWT, higher level of LVEF and lower level of NT-ProBNP compared with those in the control group(P＜0. 05). Conclusion The health education based on PRECEDE-PROCEED model is potentially effective to improve the exercise tolerance, cardiac recovery and quality of life in patients after pacemaker implantation. (目的 探讨基于格林模式的健康教育对心脏起搏器植入术后患者运动耐力及心脏功能的影响。方法 选取心脏起搏器植入术后患者98例, 按照患者入住病区, 分为对照组和试验组, 各49例。对照组实施常规健康教育, 试验组实施基于格林模式的健康教育, 两组患者干预时间均为3个月。术后3个月采用中国心血管病人生活质量评定问卷(CQQC)、6min步行试验距离(6MWT)、N端前脑钠肽(NT-ProBNP)和左心室射血分数(LVEF)进行评价。结果 术后3个月, 试验组CQQC问卷总分、6MWT距离和LVEF高于对照组, NT-ProBNP水平低于对照组, 差异有统计学意义(P＜0. 05)。结论 与常规健康教育相比较, 基于格林模式的健康教育能进一步改善心脏起搏器植入术后患者的运动耐力、心脏功能和生活质量。)